Dual-active-layer InGaZnO high-voltage thin-film transistors. (26th May 2021) - Huo, Wenxing; Liang, Huili; Lu, Yicheng; Han, Zuyin; Zhu, Rui; Sui, Yanxin; Wang, Tao; Mei, Zengxia
Abstract: InGaZnO high-voltage thin-film transistors (HV-TFTs) with vertical dual-active-layer structure and lateral offset design were fabricated at low temperature. The TFT features such as sub-threshold swing, threshold voltage, and hysteresis voltage are similar to those of the normal devices; furthermore, they are independent of the offset length. The blocking voltage of HV-TFTs with an offset of 10 μm is 406 ± 17 V while the ON/OFF ratio reaches 10 9 at V DS = 10  V .